Cassava mosaic disease resistant clones’ growth and yield are prone to early drought stress - Babirye, A.; Ntawuruhunga, Pheneas; Edema, Richard (Academic Journals, 2016)
This study was conducted to evaluate the growth and yield stability of cassava mosaic disease (CMD) resistant breeding populations clones against early drought. Field trials were planted using 200 CMD resistant clones and 7 local landraces in a randomised complete block design with 3 replicates at the International Institute of Tropical Agriculture (IITA) station, Sendusu in Namulonge (Central Uganda) during the second rains of 2006 (2006B) and the first rains of 2007 (2007A). The 2007A crop suffered from drought stress in the first 4 months after planting (MAP). Data were taken on the leaf lobe length and width at 6 MAP and plant height at 12 MAP. Harvest was done at 12 MAP during which the number of storage roots per plant and storage root yield were recorded. Data were analysed using the Mann-Whitney U test to compare crop performance between the 2 seasons. The 2006B crop had significantly (P<0.01) longer leaf lobes, taller plant heights, higher number of storage roots per plant and higher storage root yield than the 2007A crop. There was no significant difference in the leaf lobe width. In this experiment, it was observed that the CMD resistant breeding clones were susceptible to early drought and thus it was recommended that selections should be done for higher water use efficiency.